Evaluation of thermo-mechanical, dielectric and corrosion resistant properties of cardanol benzoxazine-epoxy based hybrid composites: A very low temperature curing pre-polymer for high performance paint related applications. (June 2020) - Selvaraj, V; Raghavarshini, TR; Alagar, M
In the present work, the hybrid siloxane-based cardanol-benzoxazine-epoxy (1:1 ratio) matrix (SBCBz-EP) capable of curing at substantially low temperature when compared with that of conventional benzoxazines was prepared and characterized. The matrix SBCBz-EP was reinforced with varying weight percentages (1, 3 and 5 wt%) of hydroxyl-terminated cyclotriphosphazene (HTCP) and the resulting hybrid composites were characterized by modern analytical methods, which can be used for paint-related applications due to their low-temperature curing behaviour. Data obtained from differential scanning calorimeter analysis infer that the glass transition temperature of the hybrid matrix (SBCBz-EP) and HTCP reinforced with 1, 3 and 5 wt% composites was 73°C, 75°C, 82°C, and 88°C, respectively. The polymerization temperature obtained for SBCBz-EP matrix and HTCP-reinforced hybrid composites was considerably lower than that of conventional benzoxazines. The present hybridization approach of benzoxazine and epoxy paves an avenue to alleviate the deficient characteristics of both industrially valuable resins namely high curing temperature and brittle behaviour of benzoxazines and also to improve thermal stability, mechanical strength and flame-retardant behaviour of epoxy resins. Data obtained from mechanical, dielectric, thermal stability and corrosion-resistant studies indicate that the properties of hybrid composites (HTCP/SBCBZ-EP) were enhanced to an appreciable extent according to the wt% of HTCP and it can be suggested that these hybrid composite materials can be used in the form of adhesives, sealants, encapsulants and water-resistant coatings for high performance industrial applications.